Editorial : Voices from Around the Globe (Journal of Student Affairs in Africa, 2021)
JSAA has been seeking to provide an opportunity for Student Affairs professionals and higher education scholars from around the globe to share their research and experiences of student services and student affairs programmes from their respective regional andinstitutional contexts. This has been given a specific platform with the guest-edited issue “Voices from Around the Globe” which is the result of a collaboration with the International Association of Student Affairs and Services (IASAS), and particularly with the guest editors, Kathleen Callahan and Chinedu Mba.In this respect, we are pleased that the present issue highlights the intersection of global and local issues in Student Affairs, and of debates around local professionalisation and epistemic-discursive communities of practice in Student Affairs. Global and local issues are not so much about the spatial but the framework and lens of Student Affairs, which simultaneously aim to be locally relevant and embedded, and globally referenced to an overarching set of guidelines abstracted from the local and articulated at the global. Correspondingly it is instructive to invoke the notion of the Global Gemeinschaft(Robertson, 1995) as one community in the world, with many communities inherent within it; the notion that new identity is shaped by global-international and global-local influences on the epistemic-discursive community of Student Affairs (Castell, 1997). Furthermore, the JSAA-IASAS collaborative issue also brings into focus global trends and their local expression, including the reorganisation of knowledge in Student Affairs in relation to changing local realities. By foregrounding Botswana, China, South Africa and the USA, a comparative discourse is set up which is part of the global
Keywords: JSAA; Student Affairs; International Association of Student Affairs and Services; IASAS; Global Gemeinschaft; JSAA-IASAS; Botswana; China; South Africa; USA